The total phosphorus budget of a peat‐covered catchment. Issue 7 (8th July 2016) - Worrall, Fred; Moody, Catherine S.; Clay, Gareth D.; Burt, Tim P.; Rose, Rob
Abstract: Although many studies have considered the carbon or greenhouse gas budgets of peat ecosystems, only a few have considered the nutrient budget of peat soils, and this, in turn, has limited the ability of studies to consider the impact of changes in climate and atmospheric deposition on the phosphorus budget of a peat soil. This study considered the total phosphorus (P) budget of an upland peat‐covered catchment over the period 1993 to 2012. The study has shown (i) total atmospheric deposition of phosphorus varied from 62 to 175 kg P/km 2 /yr; (ii) the carbon:phosphorus ratio of the peat profile declines significantly from values in the litter layer (C:P = 1326) to approximately constant at 30 cm depth (C:P = 4240); (iii) the total fluvial flux of phosphorus varied from 49 to 111 kg P/km 2 /yr, of which between 45 and 77% was dissolved P; and (iv) the total phosphorus sink varied from −5.6 to +71.7 kg P/km 2 /yr with a median of +29.4 kg P/km 2 /yr, which is within the range of the estimated long‐term accumulation rate of phosphorus in the peat profile of between 3 and 32 kg P/km 2 /yr. The phosphorus budget of the peat ecosystem relies on rapid recycling near the soil surface, and this means that any vegetation management may critically deprive the ecosystem of this nutrient. Key Points: First total P budget for peatland P is recycled in the shallow soil profile P is almost in equilibrium between inputs and outputs